China: Estado, universidade e empresa e sua relação com o recente crescimento econômico - Vieira, Rosilene Carla (2022)
In any field of knowledge, China is a country that sparks curiosity. After enduring historical conditions of intense submission and loss of relevance in the international sphere during the 19th and mid-20th centuries, the country continues to be increasingly recognized as a strongly industrialized global center. China’s determination is guided by five-year plans that outline how, in fewer than three decades (2049) – on the occasion of the centennial of the People’s Republic of China (PRC) – the country will conquer the status of innovative nation for investing in education and research in different fields of knowledge, particularly in Science, Technology, Engineering, and Mathematics (STEM). Those involved, therefore, include the State (defining agent and regulator of political nations), universities (principally responsible for the creation and transfer of science and technology), and enterprises which depending on the absorption of technology to maintain competitiveness increasingly. In the face of this, this thesis’ line of research query follows: how has the relationship existing between the State, universities, and enterprises contributed to China’s recent economic growth? In the search for answers, this study traverses three “paths,” organized in the form of correlated articles. For this purpose, this qualitative approach investigation, through the technique of categorical content analysis, uses bibliographic, documental and field studies (in the form of surveys and interviews). The construction of theoretical categories is based on literature related to the internationalization of higher education and the triple helix. This research reveals that contributions to the process of China’s recent economic growth have arisen, not by chance, through a virtuous yet asymmetrical relationship constructed between the State, universities, and enterprises, and that concentrate on, in order of importance, innovation in strategic sectors, increase in the economic development of the country, and a rise in the competitiveness of Chinese businesses abroad. The greatest contributions of this thesis bring light to the discussion of the relevant relationship of the triad formed between the State, universities, and enterprises, in this specific moment of China’s historical transformation, with special attention to the process of economic reform. Principally, this thesis is concerned with the comprehension of how Chinese universities are capable of contributing to the country’s forces of production. Since reopening its borders, China has not only invested in education, but it has also tied universities to its interests in external projection and its political and economic agenda. However, in the midst of China’s reinforcement of economic and political interests, it should be noted that universities are scarcely referenced in literature. This thesis about a developing country in regional and global ascendency serves as a relevant instrument to the order of public politics, and it reiterates that the development of a nation does not occur separately from education nor without planning that reflects clear directives in goal achievement.